Análise do conhecimento sobre o câncer de colo do útero: o empírico diante do científico - (:unkn) unknown (EEM - Escola de Enfermagem de Manaus, 2026)
This study aimed to analyze the level of knowledge among women regarding cervical cancer. It is an exploratory, descriptive, and qualitative research, approved by the Research Ethics Committee, conducted with 25 women aged between 25 and 64 years who attended a Health Unit in the Southern District of Manaus (AM), in January 2025. Data were collected through semi-structured interviews, and the information was analyzed according to Bardin’s Content Analysis technique. The results revealed predominantly empirical knowledge and a high demand for the preventive examination, as well as factors associated with the level of knowledge that contribute to the low adherence to other forms of prevention. It is concluded that the level of knowledge among women about cervical cancer is insufficient, especially regarding symptoms, risk factors, and prevention methods.
Analysis of knowledge about cervical cancer: empirical versus scientific perspectives
Keywords: Neoplasias; Colo do útero; Conhecimento; Mulheres; CIENCIAS DA SAUDE: ENFERMAGEM; .; .; .